Driving Waveform Optimization by Simulation and Numerical Analysis for Suppressing Oil-Splitting in Electrowetting Displays - Lai, Shufa; Zhong, Qinghua; Sun, Hailing (Frontiers in Physics, 2021)
Electrowetting display (EWD) is a new reflective display device with low power consumption and fast response speed. However, the maximum aperture ratio of EWDs is confined by oil-splitting. In order to suppress oil-splitting, a two-dimensional EWD model with a switch-on and a switch-off process was established in this paper. The process of oil-splitting was obtained by applying different voltage values in this model. Then, the relationship between the oil-splitting process and the waveforms with different slopes was analyzed. Based on this relationship, a driving waveform with a narrow falling ramp, low-voltage maintenance, and a rising ramp was proposed on the basis of square waveform. The proposed narrow falling ramp drove the oil to rupture on one side. The low-voltage maintenance stage drove the oil to shrink with a whole block. The proposed rising ramp was pushed the oil into a corner quickly. The experimental results showed that the oil splitting can be suppressed effectively by applying the proposed driving waveform. The aperture ratio of the proposed driving waveform was 2.9% higher than that of the square waveform with the same voltage.